Progression of Parkinson's disease as evaluated by Hoehn and Yahr stage transition times - Zhao, Ying Jiao; Wee, Hwee Lin; Chan, Yiong-Huak; Seah, Soo Hoon; Au, Wing Lok; Lau, Puay Ngoh; Pica, Emmanuel Camara; Li, Shu Chuen; Luo, Nan; Tan, Louis C.S. (Movement Disorders, 2010)
This study was carried out to evaluate progression in Parkinson's disease (PD) by analyzing time taken to transit from one Hoehn and Yahr (H&Y) stage to the next stage and to investigate the variables that would be associated with H&Y transition times using a large PD database that contained prospectively collected information. Data were obtained from the movement disorder database of the National Neuroscience Institute in Singapore. Kaplan-Meier (KM) survival analysis was adopted to investigate the time taken to progress through various H&Y stages. Cox regression analysis was used to examine the association between the baseline variables at the entry point of each H&Y stage and the progression to the next stage. A total of 695 patients (mean age: 65.2, male: 57.3%) were studied. Using KM analysis, the median time taken to transit from H&Y stage 1 to 2, 2 to 2.5, 2.5 to 3 were 20, 62, and 25 months, respectively; whereas the median time taken to progress from stage 3 to 4 and 4 to 5 were 24 and 26 months, respectively. Cox regression analysis revealed that older age-at-diagnosis, longer PD duration, and higher Unified Parkinson's Disease Rating Scale (UPDRS) motor scores at baseline were associated with a significantly faster progression through various H&Y stages. Gender and ethnicity were not associated with disease progression. In conclusion, H&Y transition time is a useful measure of disease progression in PD and may be utilized in clinical studies evaluating therapeutic interventions and prognostic factors in PD. © 2010 Movement Disorder Society
Keywords: H&Y; Parkinson's disease; progression